BK Polyomavirus Genotypes in Two Patients after Hematopoietic Cell Transplant - Odegard, Elizabeth A. (Microbiol Resour Announc, 2021)
BK polyomavirus (BKPyV) infection can lead to nephropathy and hemorrhagic cystitis (HC). We evaluated BKPyV genotypes in two individuals after hematopoietic cell transplant (HCT). The first case developed HC and was infected with genotype Ib-2, while the second did not develop HC and was infected with genotype Ia.